Triassic magmatism and tectonic setting of Eastern Tianshan, NW China: constraints from the geochemistry and zircon U–Pb–Hf isotopes of granitoids in the Yamansu area - Cai, Hongming; Gong, Xiangkuan; Liu, Guiping; Guo, Ruiqing; Wang, Keyong (Frontiers in Earth Science, 2023)
With an aim of providing constraints on the Triassic tectonic setting of Eastern Tianshan, an integrated study was conducted on the geochronological and geochemical data for granodiorites, monzogranites and two-mica granites from the Yamansu area on the northern margin of the Central Tianshan, NW China. Zircon U-Pb dating indicates their crystallization ages of ca. 250-241 Ma. The granodiorites (ca. 250 Ma) are medium-K calc-alkaline I-type granitoids, with crustally-derived geochemical elements ratios (e.g., Ti/Zr, Ti/Y and Nb/Ta), low Sr/Y ratios and moderate negative Eu anomalies (Eu/Eu* = 0.56-0.57), suggesting their derivation from partial melting of crustal materials with plagioclase as a major residual phase at pressure less than 12 kbar. The monzogranites (ca. 247 Ma) have adakitic characteristics, with high SiO2, but low MgO, Cr, Ni contents and low Nb/Ta ratios, indicating an origin from melts of thickened mafic lower crust at relatively high pressure (12-15 kbar). The ca. 244 Ma and ca. 241 Ma two-mica granites are high-K calc-alkaline and show geochemical features of highly fractionated I-type granites. They were generated by melting of medium- to high-K mafic to intermediate crustal rocks at pressure less than 5 kbar, accompanied mainly by feldspar fractional crystallization. All the granitoids have zircon εHf(t) values of +7.8 to +2.1, with corresponding TDM2 of 1132-773 Ma, suggesting juvenile crustal rocks as possible sources. Geochronological investigations of the studied granitoids, together with published data, suggest that the Triassic is an important period for granitic magmatism in Eastern Tianshan. Taking account into all available geological data, we suggest that the Triassic garnitoids were formed in an intracontinental environment possibly controlled mainly by far field effects of the Paleo-Tethys system, and the contemporaneous compression and extension existed at deep and shallower lithosphere depths, respectively, during Triassic.